Computational mechanics and optimization-based prediction of grain orientation in anisotropic media using ultrasonic response - Kim, Munsung; Moon, Seongin; Kang, To; Kim, Kyongmo; Song, Sung-Jin; Suh, Myungwon; Suhr, Jonghwan (Nuclear engineering and technology, 2021)
Ultrasonic nondestructive testing is important for monitoring the structural integrity of dissimilar metal welds (DMWs) in pressure vessels and piping in nuclear power plants. However, there is a low probability of crack detection via inspection of DMWs using ultrasonic waves because the grain structures (grain orientations) of the weld area cause distortion and splitting of ultrasonic beams propagating in anisotropic media. To overcome this issue, the grain orientation should be known, and a precise ultrasonic wave simulation technique in anisotropic media is required to model the distortion and splitting of the waves accurately. In this study, a method for nondestructive prediction of the DMW grain orientations is presented for accurate simulation of ultrasonic wave propagation behavior in the weld area. The ultrasonic wave propagation behavior in anisotropic media is simulated via finite-element analysis when ultrasonic waves propagate in a transversely isotropic material. In addition, a methodology to predict the DMW grain orientation is proposed that employs a simulation technique for ultrasonic wave propagation behavior calculation and an optimization technique. The simulated ultrasonic wave behaviors with the grain orientations predicted via the proposed method demonstrate its usefulness. Moreover, the method can be used to determine the focal law in DMWs.